Sustainable production of DMF and EMF using inulin-rich raw plant biomass: Perspective towards biorenewable fuel. (10th May 2022) - Lee, Jin-Woo; Lee, Yong-Suk; Chung, Chung-Han
Abstract: 2, 5-Dimethyfuran (DMF) and ethoxymetylfurfural (EMF) are the emerging potential bio-based fuel candidates that can replace petro-based ones. These fuels possess physicochemical properties comparable to those required in gasoline engine performance, but they have more favorable properties than bioethanol. In current, two types of input substrates, hydroxylmethylfurfural (HMF) and fructose-based feedstocks are used to produce these fuel candidates due to their higher production efficiency. This bio-based production process has advantages in the sustainability point of view due to the low-carbon economy and resource renewability, but its economic issue is a significant roadblock in their industrial production mainly due to high production costs. Our proposed strategies afford significant information about their cost-effective production processes. One approach is to apply the direct conversion technology of inulin-rich raw plant biomass to these biofuels. Their direct use eliminates several processing steps required in the production process of both biofuels, contributing to reduction of their production costs The processes proposed can be performed in one-step processing systems consisting of 3–4 reaction elements: Feeding substrate, ionic liquid solvent, selected catalysts, and/or ethanol/additive. Their admixture is directly processed to the final products under the given reaction condition with no separation step of the major intermediates (e.g., HMF) occurring during the processing. The proposed strategies are less complicated and straightforward processes that have not been attempted before. Together with these strategies, bioengineering strategies are introduced for facilitating the efficiency of production processing and improving inulin content of the target plants, which can conduce to reducing their production costs. Highlights: Inulin-rich plants could be the biomaterials for production of DMF and EMF. The proposed bioprocess contributes to reducing the production cost o DMF and EMF. The proposed bioprocess contributes to the mitigation of CO2 emissions. The biostrategy conduces to improving the production efficiency of DMF and EMF.